2005
DOI: 10.1590/s0004-27492005000500004
|View full text |Cite
|
Sign up to set email alerts
|

Topographic corneal changes in patients with vernal keratoconjunctivitis

Abstract: Results of this study suggested high frequency of patients with keratoconus associated with vernal keratoconjunctivitis. Visual performance is compromised by aberrations and changes in corneal asphericity and other topographic variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 17 publications
5
43
1
2
Order By: Relevance
“…VKC often presents as a relatively benign and self limited condition, disabling lesion such as corneal ectasia have been reported descriptively as a complication of severe and prolonged VKC [7,8]. Chronic ocular trauma and rubbing of eye due to pruritus could be the environmental factor ("trigger") associated with keratoconus development in genetically predisposed individuals [7].…”
Section: Introductionmentioning
confidence: 99%
“…VKC often presents as a relatively benign and self limited condition, disabling lesion such as corneal ectasia have been reported descriptively as a complication of severe and prolonged VKC [7,8]. Chronic ocular trauma and rubbing of eye due to pruritus could be the environmental factor ("trigger") associated with keratoconus development in genetically predisposed individuals [7].…”
Section: Introductionmentioning
confidence: 99%
“…(11)(12)(13)(14)(15)(16) All studies reported late presentation of keratoconus in VKC patients except Gortzak et al (15) Dantas et al report, palpebral VKC (97.81%) was more common in patients having keratoconus whereas mixed VKC (36.50%) was more common in our study. (17) Sixty four (30.47%) were found to have suspected keratoconus-like topography as compared to 10.7% by clinical criteria in our study. Slit lamp confirmed cases account for 10 of the 30 cases.…”
Section: Discussionmentioning
confidence: 55%
“…(15) Dantas et al reported 22.53% of keratoconus by videokeratographic maps and 9.85% clinically by slit lamp examination in VKC patients. (17) Total et al detected 26.8% of keratoconus by videokeratography maps and 8.5% clinically by slit lamp examination in VKC. (14) These studies used the modified Rabinowitz-McDonnell criteria.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nas conjuntivites alérgicas, a presença de síndrome do olho seco e ceratocone têm sido descritas, bem como tem sido observada a evolução mais precoce de ceratocone em pacientes com CCV 4,20,46 . Da mesma forma, o uso exagerado de aparelhos eletrônicos, tem sido implicado como fator associado ao crescente número de pessoas com síndrome do olho seco, e por conseguinte deve ser considerado fator agravante das síndromes alérgicas 47,48 .…”
Section: Alergia Ocularunclassified